If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13z + 13 = 26 Reorder the terms: 13 + -13z = 26 Solving 13 + -13z = 26 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -13z = 26 + -13 Combine like terms: 13 + -13 = 0 0 + -13z = 26 + -13 -13z = 26 + -13 Combine like terms: 26 + -13 = 13 -13z = 13 Divide each side by '-13'. z = -1 Simplifying z = -1
| -3(4n+6)=-6(n-8) | | .03x+.05(200-x)=9 | | 7m-25=-4 | | 2m+20=26 | | X^2-8x-4=-11 | | 3.3=1.5-0.4 | | x+4k=0 | | -18=x-5 | | -15x+25=-95 | | 9z-17=-35 | | 10y-2=48 | | -11y-9=-86 | | -15p-1=-46 | | 31-3n=4(n+6) | | C+32=-8 | | (5x^3+1)-1=0 | | 3822/14 | | 60.00+42.95p=25.00+49.95p | | -4y-13=15 | | 10x-11=-1 | | -2(n-5)=3n(n-6) | | -13x+15=-63 | | x-.20x=366 | | x-.20x=390 | | 8p-3=77 | | x-20x=390 | | 6(1-4v)=3(4-7v) | | -8x+8x-21=-12-16 | | -y+20=12 | | 99=11m | | 7p+3=-53 | | 2x+5-3=3 |